Penguatan Profil Pelajar Pancasila melalui Budaya Sekolah Bernuansa Islami di SMAN 1 Kecamatan X Koto - Nur, Karmila Muhammad; Rivauzi, Ahmad (ALSYS, 2024)
This research aims to describe the implementation of an Islamic nuanced school culture in strengthening the profile of Pancasila students, as well as analyze the supporting and inhibiting factors in strengthening the profile of Pancasila students through an Islamic nuanced school culture. The method used is qualitative research with a case study approach. The informants in the research are the school principal, student representatives, curriculum representatives, and class XI students. . Data collection techniques used were interview, observation, and documentation methods. Data analysis is carried out through data reduction, data display, and drawing conclusions. Data validity techniques use source triangulation and technical triangulation. The results of this research indicate that there are three aspects that need to be considered in implementing an Islamic school culture to strengthen the Pancasila student profile, namely the learning process, raising awareness, and monitoring the values of the Pancasila student profile. The supporting factors in strengthening the profile of Pancasila students are the cooperation of teachers with the student council and support from the surrounding community, while the inhibiting factors are the lack of awareness of students in implementing an Islamic school culture and the lack of supervision from teachers and parents.